2012
DOI: 10.1212/wnl.0b013e31824f807a
|View full text |Cite
|
Sign up to set email alerts
|

Long-term risk of developing epilepsy after febrile seizures

Abstract: The risk of developing epilepsy in people who had febrile seizures seems to decrease with time. Further long-term studies are needed to confirm this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 17 publications
1
33
0
3
Order By: Relevance
“…For example, after a febrile convulsion, the risk of developing epilepsy is 6%, reducing over time. 68 imaging or electroencephalographic abnormalities (spikes, slow waves, or both) are the strongest predictors of recurrence across many studies. 70 For patients with one or both of these factors, the risk of recurrence is 70% over five years.…”
Section: Is This a First Seizure And Will It Recur?mentioning
confidence: 99%
“…For example, after a febrile convulsion, the risk of developing epilepsy is 6%, reducing over time. 68 imaging or electroencephalographic abnormalities (spikes, slow waves, or both) are the strongest predictors of recurrence across many studies. 70 For patients with one or both of these factors, the risk of recurrence is 70% over five years.…”
Section: Is This a First Seizure And Will It Recur?mentioning
confidence: 99%
“…In addition, studies with the general population have established history of febrile seizures as a factor leading to development of non-febrile seizures later in life [18, 19]. Lastly, a study by Wang et al (2011) found higher prevalence of GI dysfunctions in children with ASD compared to their ASD unaffected siblings, indicating the importance of controlling for GI status when assessing relative prevalence of seizures in ASD [6].…”
Section: Resultsmentioning
confidence: 99%
“…Yet such distinction is critical since the pathophysiology and risk factors associated with febrile seizures differ from other types of seizures, and febrile seizures are known to increase the risk of developing non-febrile seizures later in life [1820]. Also, when assessing seizure prevalence, it is important to distinguish whether the ASD diagnosis is primary (idiopathic) or secondary to another neurological disorder (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of recurrent FS after a first seizure is about 30-40%, but the risk of subsequent epilepsy is only slightly increased since simple FS are followed by epilepsy in less than 2% of patients, which is similar to the risk in the general population [3,4]. However, a higher proportion of patients develop epilepsy following complex FS, with the reported incidence ranging from 4.1% to 7% [4,5].…”
Section: Introductionmentioning
confidence: 80%